Design and Simulation of an Electromagnetic Penta-Perfect Metamaterial Absorber for Microwave Application - Albadri , Raed Ashraf Kamil; Al-Badri , Khalid Saeed Lateef (Advances and Challenges in Science and Technology Vol. 3, 2023)
Utilizing a multiband metamaterial absorber has diverse applications across various fields due to its unique electromagnetic properties. Some key applications include: Radar Cross-Section (RCS) Reduction, Stealth Technology, Electromagnetic Compatibility (EMC), Antenna Design, Medical Imaging, Energy Harvesting, Aerospace Engineering, Material Testing. This chapter presents a straightforward simulation of a multi-band metamaterial absorber intended for microwave frequencies. The proposed unit cell is composed of two copper rings placed at different radii on an FR4 substrate with a thickness of 2.5 mm, enabling the creation of multiple absorption bands. While the conventional asymmetrical ring structure often responds to electromagnetic (EM) wave polarization, the innovative Penta-Perfect Metamaterial Absorber (PPMMA) structure introduced in this study showcases the capacity to effectively absorb EM waves across a broad range of incident angles. According to CST simulation outcomes, the PPMMA structure exhibits five distinct absorption bands, achieving complete metamaterial absorption for normally incident electromagnetic waves at frequencies of 12.25 GHz (absorbance of 91.3%), 12.9 GHz (absorbance of 99.3%), 16.15 GHz (absorbance of 93.7%), 16.78 GHz (absorbance of 98.2%), and 18.44 GHz (absorbance of 97.4%).